Fleksibilitas Dan Tantangan Implementasi Kurikulum Merdeka Dalam Pembelajaran Bahasa Indonesia di SDN 060877 Medan - Mutiah Dina Maya; Muhammad Rif’an; Shaqila Rizky D.A; Riani Tazkia Hadi; Ibrahim Gultom; Muhammad Ikhlas (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the implementation of the Independent Curriculum in Indonesian language learning in class 4B of SDN 060877 Medan, with a focus on curriculum flexibility and challenges in meeting students' needs. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Independent Curriculum provides flexibility for teachers in adjusting teaching methods and materials according to students' needs. Teachers can adapt a more contextual, creative, and innovative approach. However, the main obstacles found were students who were not yet fluent in reading, lack of motivation to learn, and minimal support from the family environment. To overcome this, teachers apply differentiated learning strategies, use of appropriate teaching modules, and interactive methods to improve students' literacy skills. In addition, additional assistance is provided for students who have difficulty understanding the material. Despite facing various challenges, the Independent Curriculum is still considered more effective in supporting the achievement of students' competencies optimally, especially in improving their understanding and literacy skills. With support from various parties, it is hoped that learning will be of better quality and in accordance with students' needs.